Sikap Sosio-Spritual Dalam Akuntansi Kontemporer: Telaah, Tantangan Dan Imajinasi Diri - Diah Hari Suryaningrum (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2011)
AbstractThis paper is attempted to explore, challenge, and imagine contemporary accounting and its role in socio-spiritual manner. In exploring contemporary accounting such as social accounting and spiritual accounting, I found that their emerging in new accounting is really needed. Even if social accounting have been found centuries ago, their development is increased when people aware not only that their action is affected in economy wealth, it is also influenced their social, environmental, and sustainability development. Accounting is trying to measure this externalities cost. Some are skepticism with the effort since in reducing these externalities of environmental destructions; it will not support the notion of social contract. Likewise, spiritual accounting is also trying to concern for others but in a spiritual point of view. This new development in accounting is a challenge for accounting profession in a way how they have to behave. Accountants not only have to obey to accounting profession code of ethics, they also have to practice accounting in their socio-spiritual manner. This paper is concluded with the notion that whatever role accounting choose, it is up to the accountant to take part in that role.